Integrasi Konstitusi Hijau dalam Era Society 5.0 Tantangan dan Peluang dalam Pengelolaan Lingkungan - Asti Sri Mulyanti; Syavira Azzahra, Syavira Azzahra (KRTHA BHAYANGKARA, 2024)
The legal framework must adapt to technological advances and environmental sustainability demands during the Society 5.0 era. This research looks at how to use the green constitution to deal with the challenges and opportunities offered by Society 5.0. The purpose of this study is to see how a green constitution can be incorporated into the legal system to ensure a balance between technological advancement and environmental protection and to see how it can impact legal policies and practices in different countries. This research uses a thorough normative analysis method of the latest literature that discusses the green constitution, environmental law, and Society 5.0. The study also includes a comparative analysis of the implementation of green constitutions in several international jurisdictions. Furthermore, the data collected from this literature research is analyzed to find relevant trends, problems, and innovative solutions. This research shows that incorporating a green constitution into the legal framework of Society 5.0 can encourage sustainable technological advancement and improve environmental protection. The study also shows that policymaking that incorporates green principles in law can improve regulatory efficiency and drive the achievement of broader sustainability goals.